Copper Toxicity And Its Medicolegal Aspects: A Review - Tiwari, Alok Kumar; Inchulkar, S R; Bhagat, Sangeeta (International Research Journal of Ayurveda & Yoga, 2021)
Copper may not be self-injected for sucidial or self harm because of the colour and taste. In most of cases accidental poisoning occurs. Accidental poisoning results from eating food contaminated with Verdigris which is formed from the action of vegetable acids on copper cooking vessels which are not properly tinned on the inside. A number of adverse health effects can result from excessive copper levels including damage to kidneys and liver, anemia, immuno-toxicity and developmental toxicity. Copper affects virtually everybody system directly or indirectly. Copper-mediated deficiency, or deficiency of vitamin C, folic acid, or other nutrients induced by copper toxicity, is responsible for many symptoms associated with copper toxicity. The aim of this review is to focus on the diagnostic difficulties facing coroners and forensic pathologists when the court reguire confirmation. Forensic examination performed on the corpses of victims who died in or out of hospital or on surviving injured or intoxicated victims showing signs of metal poisoning, demands the careful evaluation of the death scene, all related circumstances and of clinical and autopsy data. Close interaction between forensic pathologist and toxicologist is also needed to identify and quantify copper levels in blood, urine and tissues.